Sistem Pendukung Keputusan untuk Pengoptimalisasi Pemilihan Supplier Menggunakan Metode SAW pada Baking Daily Store - Ryan Fakhroji; Aan Risdiana; Achmad Birowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The problem faced by Baking Daily Store is that there is no system that can be used to optimize supplier selection, which has only been done based on intuition and relationships. This has the potential to cause inefficiencies in supplier selection which have an impact on the availability of raw materials, product quality, and timeliness of delivery. Therefore, a decision support system was designed to help Baking Daily Store in choosing the best supplier objectively, quickly, and accurately. This system applies the Simple Additive Weighting (SAW) method to perform calculations and assessments based on predetermined criteria. The result of this system development is a desktop-based application using the Java programming language, which is expected to help management in making decisions in a more measurable and structured manner.